Global, regional, and national trends in gastric cancer burden: 1990-2021 and projections to 2040 - Zhang, Tao; Zhang, Yiqun; Leng, Xiaofei (Frontiers in Oncology, 2024)
BackgroundGastric cancer (GC) is a common malignancy of the digestive system, with significant geographical variation in its disease burden.MethodsThis study used data from the Global Burden of Diseases, Injuries, and Risk Factors Study 2021 to analyze three key indicators: incidence, mortality, and disability-adjusted life years (DALYs). Initially, a detailed analysis of the GC burden was conducted from global, regional, national, gender, and age perspectives. Subsequently, the percentage change and average annual percent change (AAPC) of GC were calculated to understand the trends in disease burden. Decomposition analysis and frontier analysis were then performed. Finally, the Bayesian age-period-cohort model was used to predict the trends in age-standardized rates (ASRs) of GC up to 2040.ResultsIn 2021, there were 1.23 million (95% UI: 1.05-1.41 million) new cases of GC globally, with 0.95 million (95% UI: 0.82-1.10million) deaths and 22.79 million (95% UI: 19.58-26.12 million) DALYs. Compared to 1990, the global ASRs of GC has declined, but new cases and deaths have increased. For females, age-standardized incidence rate, age-standardized mortality rate, and age-standardized DALYs rate were 8.6, 7.1, and 165.6 per 100,000, with AAPCs of -2.1, -2.4, and -2.6. For males, they were 20.9, 16.0, and 371.2 per 100,000, with AAPCs of -1.6, -2.1, and -2.3. ASRs fluctuated with increasing Socio-demographic Index (SDI), being higher in middle and high-middle SDI regions. Decomposition analysis indicated negative effects from epidemiological trends on GC burden, while population growth and aging had positive effects. Frontier analysis showed that middle and high-middle SDI regions had more potential for reducing ASRs. Predictions indicate a continued decline in ASRs for both genders by 2040.ConclusionDespite progress in controlling GC, the number of new cases and deaths globally is rising due to population growth and aging. This highlights the need for effective prevention and control strategies.